2011
DOI: 10.1146/annurev-bioeng-071910-124706
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Models of Traumatic Brain Injury

Abstract: In vitro models of traumatic brain injury (TBI) are helping elucidate the pathobiological mechanisms responsible for dysfunction and delayed cell death after mechanical stimulation of the brain. Researchers have identified compounds that have the potential to break the chain of molecular events set in motion by traumatic injury. Ultimately, the utility of in vitro models in identifying novel therapeutics will be determined by how closely the in vitro cascades recapitulate the sequence of cellular events that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
176
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(182 citation statements)
references
References 205 publications
3
176
0
3
Order By: Relevance
“…loss of action potentials) but also functional response such as synaptic and white matter plasticity, and long term potentiation and depression 28,[55][56] . In vitro brain slice and the recently emerging organ-on-chip and human-on-chip technologies [57][58][59] provide foundation for the development of 'living', 'humanised' brain-on-chip devices that could be used to investigate various primary and secondary injury mechanisms but also responses to treatments such as hypothermia, electro/magnetic stimulation and pharmacological interventions. Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…loss of action potentials) but also functional response such as synaptic and white matter plasticity, and long term potentiation and depression 28,[55][56] . In vitro brain slice and the recently emerging organ-on-chip and human-on-chip technologies [57][58][59] provide foundation for the development of 'living', 'humanised' brain-on-chip devices that could be used to investigate various primary and secondary injury mechanisms but also responses to treatments such as hypothermia, electro/magnetic stimulation and pharmacological interventions. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental in vitro and animal models of TBI have shown that the primary microdamage to various neuro-structures initiates a cascade of biophysical and neurochemical events, lasting from minutes to hours, resulting in either axonal, synaptic and vascular repair or permanent damage [59][60] . Development of secondary injury models involves construction of a conceptual mechanistic model of injury mechanisms, mathematical formulation of the underlying mechano-biology model and calibration/ validation of the model on available in vitro experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…advantageous complements when it comes to exploration of isolated phenomena. Moreover, in vitro models are easy to use, affordable, less ethically challenged, reproducible and better controlled, and re present a good platform for drug screening (21)(22)(23). Hence, in vitro models of TBI are a variable tool in studying the pathobiology beyond brain injury and there is a need to define them more profoundly.…”
Section: Discussionmentioning
confidence: 99%
“…A number of in vitro models have been introduced in order to reproduce the features of interest in an isolated system and to allow manipulations, monitoring on multiple levels in real time, while being precisely controlled (11,12). One of such is a scratchwound assay (SW), first established as a simple, reproducible assay for the analysis of cell migration in vitro (13).…”
Section: Kratak Sadr`ajmentioning
confidence: 99%
“…Numerous studies show that even mild concussions, if induced repeatedly, can lead to permanent brain damage; the issue is constantly debated in the sports media, but especially in football [17]. The pathophysiology of TBI is heterogeneous [18,19,16]. However, all severities of TBI trigger axonal damage widespread over a large number of neurons [20].…”
Section: Introductionmentioning
confidence: 99%